Maternal Choline Supplementation and High-Fat Feeding Interact to Influence DNA Methylation in Offspring in a Time-Specific Manner - Korsmo, Hunter W.; Dave, Bhoomi; Trasino, Steven; Saxena, Anjana; Liu, Jia; Caviglia, Jorge Matias; Edwards, Kaydine; Dembitzer, Moshe; Sheeraz, Shameera; Khaldi, Sarah; Jiang, Xinyin (Frontiers in Nutrition, 2022)
Maternal methyl donor supplementation during pregnancy has demonstrated lasting influence on offspring DNA methylation. However, it is unknown whether an adverse postnatal environment, such as high-fat (HF) feeding, overrides the influence of prenatal methyl donor supplementation on offspring epigenome. In this study, we examined whether maternal supplementation of choline (CS), a methyl donor, interacts with prenatal and postnatal HF feeding to alter global and site-specific DNA methylation in offspring. We fed wild-type C57BL/6J mouse dams a HF diet with or without CS throughout gestation. After weaning, the offspring were exposed to HF feeding for 6 weeks resembling a continued obesogenic environment. Our results suggest that maternal CS under the HF condition (HFCS) increased global DNA methylation and DNA methyltransferase 1 (Dnmt1) expression in both fetal liver and brain. However, during the postnatal period, HFCS offspring demonstrated lower global DNA methylation and Dnmt1 expression was unaltered in both the liver and visceral adipose tissue. Site-specific DNA methylation analysis during both fetal and postnatal periods demonstrated that HFCS offspring had higher methylation of CpGs in the promoter of Srebf1, a key mediator of de novo lipogenesis. In conclusion, the influence of maternal CS on offspring DNA methylation is specific to HF feeding status during prenatal and postnatal periods. Without continued CS during the postnatal period, global DNA methylation enhanced by prenatal CS in the offspring was overridden by postnatal HF feeding.